(untitled) (Religion, Culture, and State Journal, 2022)
What causes radicalisation and violent extremism to emerge? Such a question has been the forefront of the world’s political agenda as the sense of urgency surrounding terrorism continue to rise. Schools of research have been conducted to reveal social and psychological factors motivating individuals to adopt the ideologies related to violent extremism and radicalisation. However, comprehensive conclusions translatable to policy making are still lacking. In fact, to be able to effectively and expediently address the underlying issues, we must all stand on a common ground, namely, we must return to the starting point of each individual: the family. We must then consider a potential key actor in their pursuit of a potential solution: mothers. Therefore, the purpose of this explanatory study is to investigate mothers’ perception on what causes violent extremism and what actions they should undertake to tackle the issue. A multiple-case study design was used. Eight randomly selected mothers whose children are in their adolescent within Babakan sub-urban area of Mataram city, West Nusa Tenggara, participated. Data were obtained from individual, digitally recorded face-to-face semi-structured interviews. The findings from this explanatory study suggest that the women had moderate knowledge towards violent extremism and radicalisation and aware of their critical roles in preventing their children from exposure to terrorism-related ideologies. Further, the study provides insights into how male domination tends to prevent the women to play the key roles in countering terrorism as, in local context, the issues related to this are sound rather masculine.